On the Pathomorphological Pattern of the Efficiency of Photodynamic Therapy of Murine Melanoma B16 Using a New Photosensitizer Based on Chlorin e6 Conjugate with a Prostate-Specific Membrane Antigen - Olga B. Abramova; Grigory A. Demyashkin; Valentina V. Drozhzhina; Nina D. Yakovleva; Ekaterina A. Kozlovtseva; Tatiana P. Sivovolova; Petr V. Shegay; Sergey A. Ivanov; Andrey D. Kaprin (Molecules, 2022)
Photodynamic therapy (PDT) is an effective treatment for a number of solid malignancies. In this work, the antitumor efficacy of photodynamic therapy for murine B16 melanoma with intravenous administration of a new photosensitizer (PS) based on the chlorin e6 conjugate with a prostate-specific membrane antigen (PSMA) was studied in vivo. We have previously published the data obtained in the first part of the study: the dynamics of PS accumulation in the tumor and surrounding tissues and the antitumor efficacy of the photodynamic therapy, which was evaluated by the regression parameters and morphological characteristics of the tumors—including by the complete regression of the tumors, the absolute growth rate of the tumors among the mice with continued tumor growth, and an increase in life expectancy compared to the control. The criterion for a complete cure was the absence of signs of tumor recurrence within 90 days after therapy. The conducted studies demonstrated the high efficiency of the new photosensitizer for the photodynamic therapy of B16 melanoma. This article presents a continuation of this work, including histological studies of the zones exposed to laser irradiation on the 21st day after treatment and an assessment of the therapeutic potential of photodynamic therapy for the destruction of tumor cells. Pathological studies in the zones of photodynamic exposure revealed that the effectiveness of the PDT depended on the PS dose and the laser irradiation parameters.